Clinical Spectrum of Pediatric Coronavirus Disease 2019 Infection - Eun Lee; Soo-Jong Hong (Pediatric Respirology and Critical Care Medicine)
Since December 2019, coronavirus disease 2019 (COVID-19) cases have been reported. The clinical features of COVID-19 in children are different from those in adults including morbidity and mortality. Even in infants and children, the clinical features are different according to ages in some cases. The children are commonly coinfected to diverse respiratory viruses, and therefore physicians, who take care of infants and children infected with COVID-19, have to consider diverse clinical aspects in their patients infected with COVID-19. In this review, we have summarized the clinical features of COVID-19 in children.